Exploring the Role of Channel Integration Quality in Enhancing Relationship Quality and Customer Engagement: A Qualitative Study (International Journal of Scientific Research and Management (IJSRM), 2025)
In the past few decades, marketing channels have undergone significant changes and reforms in terms of their concept, purpose, usage, structure, formation, functionality, and interactivity, resulting in a notable deviation from traditional channel design to omnichannel retail. Merely considering omnichannel integration alone is insufficient to address consumer behavior. It’s crucial to analyze the influence of all stakeholders in order to understand how companies adapt their services to satisfy customer expectations in response to market changes like COVID-19. Therefore, this paper examines the link between channel integration quality and relationship quality with their crucial role in enhancing customer engagement. We have proposed a novel integrated conceptual model that has never been evaluated in the literature addressing the influence of channel integration quality on relationship quality. We have adopted a qualitative study to validate our conceptual framework hypotheses, and the findings were very promising.